Enhancing first-year engineering design through an integrated storytelling framework - de Freitas, Claudio (Frontiers in Education, 2026)
This study explores how storytelling can support first-year engineering (FYE) students’ learning of the Engineering Design Process (EDP) when combined with Project-Based Learning (PJBL), Community-Based Learning (CBL), and Team-Based Learning (TBL). In a FYE course, students worked in teams as fictional engineering companies, assumed professional roles, and completed projects for both fictional and real clients. Using a quasi-experimental pre–post design with surveys (N = 64 complete responses) and reflective prompts (N = 78), we examined changes in students’ perceptions of engineering design. Quantitative findings showed significant gains in familiarity with EDP steps, confidence in applying the process to real-world problems, and recognition of creativity, sustainability, and teamwork as central to engineering. Items on ethics, innovation, and everyday applications showed no significant change. Qualitative analysis identified four themes: identity and authenticity, motivation and engagement, understanding of the design process, and preparedness for real-world challenges. Together, the results suggest that storytelling, when integrated with PJBL, CBL, and TBL, enhances engagement and fosters professional identity development in first-year engineering students.